Correction: Enantioselective copper catalysed intramolecular C–H insertion reactions of α-diazo-β-keto sulfones, α-diazo-β-keto phosphine oxides and 2-diazo-1, 3-diketones; the influence of the carbene substituent. Issue 5 (17th January 2019) - Shiely, Amy E.; Slattery, Catherine N.; Ford, Alan; Eccles, Kevin S.; Lawrence, Simon E.; Maguire, Anita R.
Abstract : Correction for 'Enantioselective copper catalysed intramolecular C–H insertion reactions of α-diazo-β-keto sulfones, α-diazo-β-keto phosphine oxides and 2-diazo-1, 3-diketones; the influence of the carbene substituent' by Amy E. Shiely et al., Org. Biomol. Chem., 2017, 15, 2609–2628.